Paraneoplastic dermatomyositis and Hodgkin’s lymphoma in a 14-year-old girl: a case report and literature review - Ling, Yanyan; Hu, Huaiqiang; Xu, Xiangyan; Feng, Jianli; Li, Mingzhe; Li, Huan; Cheng, Ming; Wang, Xiaoling (Frontiers in Oncology, 2024)
Background: Juvenile dermatomyositis (JDM) is a rare autoimmune myopathy whose main clinical manifestations include a characteristic rash, symmetrical proximal muscle weakness, and elevated muscle enzymes. While approximately one-third of adult patients with dermatomyositis (DM) develop malignancies, typically within a year of diagnosis, this phenomenon is not commonly observed in patients with JDM. In this study, we present a rare case of both JDM and Hodgkin's lymphoma (HL) diagnosed in an adolescent female patient.Case description: A 14-year-old girl with proximal muscle weakness and myalgia for 8 weeks was admitted to the hospital and ultimately received a diagnosis of DM. A thorough physical examination revealed enlarged lymph nodes on both sides of the cervical, and a lymph node biopsy was performed to diagnose HL. After she underwent radiotherapy and chemotherapy, her symptoms of both HL and DM were alleviated.The phenomenon of JDM as a paraneoplastic syndrome associated with HL is very rare. Thus, routine cancer screening for DM in adolescents is currently not recommended. The diagnosis of JDM requires a detailed physical examination, and further tumor screening is necessary for patients with unusual physical findings, such as atypical rashes, enlarged lymph nodes, and enlargement of the spleen and/or liver.Even if no malignancy is detected when JDM is diagnosed, long-term follow-up is necessary.